PERAN ORGANIZATIONAL CITIZENSHIPP BEHAVIOR SEBAGAI MEDIATOR DENGAN ANTECEDENT EMOTIONAL QUOTIENT DAN SPIRITUAL QUOTIENT PADA KINERJA KARYAWAN - Adjie, Kemal Setia; Risyanti, Yustina Denik; Samtono, Samtono; Supriyanto, Sapto (ITB AAS Indonesia Surakarta, 2024)
In an effort to understand how Emotional Quotient (EQ) and Spiritual Quotient (SQ) affect employee performance with organizational citizenship behavior (OCB) as a mediator in higher education institutions, quantitative methods were chosen for use in this study. A total of 72 employees were selected as a sample in the study conducted. Questionnaires are selected as data collection methods, and tested and analyzed with multiple linear regression methods using SPSS. Regression analysis shows that OCB plays a role as an intervinning variable on relationship between EQ and SQ to employee performance. So that to improve employee performance, that is necessary to increase EQ, SQ and OCB